Bahasa Inggris - Nurlela, Heni; Handayani, Tuty (Elite : English and Literature Journal, 2024)
This research examines the assertive acts employed by Joe Biden during his first interview as President on the 60 Minutes YouTube Channel. Using Searle & Vanderveken’s theory of speech acts, the study adopts a qualitative descriptive approach. Data collection involved watching videos, reading the transcript, and note-taking. The analysis identified 20 utterances which are categorized into eight types of assertive acts: admit, assure, claim, criticize, inform, rebut, report, and predict. The most frequently used of assertive act was “inform”, with 7 utterances, followed by "assure" with 3 utterances. Other acts such as “report”, “predict”, “claim”, and “admit” each appeared twice, while “criticize” and "rebut" were used once each. The study found that all assertive acts, except "criticize," were conveyed directly and literally. In conclusion, Joe Biden conveyed assertive acts by utilizing direct speech and literal meanings to effectively convey his message, particularly in assuring the public of his plans to address the COVID-19 pandemic.